2005
DOI: 10.1111/j.1474-9726.2005.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, physical, and demographic changes in Drosophila populations through dietary restriction

Abstract: SummaryDietary restriction (DR) is a valuable experimental tool for studying the aging process. Primary advancement of research in this area has relied on rodent models, but attention has recently turned toward Drosophila melanogaster . However, little is known about the baseline effects of DR on wild-type Drosophila and continued experimentation requires such information. The findings described here survey the effects of DR on inbred, wildtype populations of Canton-S fruit flies and demonstrate a robust effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 21 publications
13
109
4
1
Order By: Relevance
“…In fact, males in mixed-sex groups on restricted diets without methionine had lower average lifespan compared to the 1.0 diet. In contrast, other studies have found a positive effect of DR on male lifespan (Magwere et al 2004;Bross et al 2005;Dick et al 2011). As it stands, we Further studies are necessary to confirm this finding, but our results highlight that nutritional effects can be sex-specific and that it is possible for lifespan-extending genetic or environmental manipulations to be only successful in one sex, with a negative or no effect on the other sex.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In fact, males in mixed-sex groups on restricted diets without methionine had lower average lifespan compared to the 1.0 diet. In contrast, other studies have found a positive effect of DR on male lifespan (Magwere et al 2004;Bross et al 2005;Dick et al 2011). As it stands, we Further studies are necessary to confirm this finding, but our results highlight that nutritional effects can be sex-specific and that it is possible for lifespan-extending genetic or environmental manipulations to be only successful in one sex, with a negative or no effect on the other sex.…”
Section: Discussioncontrasting
confidence: 56%
“…Males are rarely used in Drosophila aging studies but see (Magwere et al 2004;Bross et al 2005;Dick et al 2011) and almost never in different social environments. In our study, males on restricted diets did not have higher average lifespan compared to the 1.0 diet.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to one study in flies, in which DR only changed the short-term risk/initial mortality rate with no change in age-dependent acceleration of mortality rate [4], but consistent with a different study in flies [5]. While the present manuscript was being prepared, results consistent with the present study were published [8].…”
Section: Discussionsupporting
confidence: 87%
“…For rats, it is clear that dietary restriction (DR) decreases senescence [3] (Yen et al unpublished) but not initial mortality rate, but for mice and fruit flies, the relationship is more ambiguous. One study has shown that DR in fruit flies decreases initial mortality rate and not the agedependent acceleration of mortality rate [4], but another study in flies suggests the opposite [5]. Studies in mice have also produced conflicting results about the effects of DR on initial mortality rate and age-dependent acceleration of mortality rate (Yen et al unpublished) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1a-d). The base and DR diets used here are routinely employed in aging intervention and DR studies in D. melanogaster (Bross et al 2005;Bass et al 2007a;Zou et al 2007). Our findings suggest that supplementation of resveratrol at up to 200 μM is not sufficient to promote longevity of flies under standard or restricted dietary conditions.…”
Section: Resultsmentioning
confidence: 99%